Process evaluation of the scale-up of integrated diabetes and hypertension care in Belgium, Cambodia and Slovenia (the SCUBY Project): a study protocol - Josefien van Olmen; Kerstin Klipstein-Grobusch; Por Ir; Wim Van Damme; Roy Remmen; Edwin Wouters; Veerle Buffel; Srean Chhim; Grace Marie V Ku; Daniel Boateng; Monika Martens; Zalika Klemenc Ketiš; et al. (BMJ Open)
Introduction Integrated care interventions for type 2 diabetes (T2D) and hypertension (HT) are effective, yet challenges exist with regard to their implementation and scale-up. The ‘SCale-Up diaBetes and hYpertension care’ (SCUBY) Project aims to facilitate the scale-up of integrated care for T2D and HT through the co-creation and implementation of contextualised scale-up roadmaps in Belgium, Cambodia and Slovenia. We hereby describe the plan for the process and scale-up evaluation of the SCUBY Project. The specific goals of the process and scale-up evaluation are to (1) analyse how, and to what extent, the roadmap has been implemented, (2) assess how the differing contexts can influence the implementation process of the scale-up strategies and (3) assess the progress of the scale-up.Methods and analysis A comprehensive framework was developed to include process and scale-up evaluation embedded in implementation science theory. Key implementation outcomes include acceptability, feasibility, relevance, adaptation, adoption and cost of roadmap activities. A diverse range of predominantly qualitative tools—including a policy dialogue reporting form, a stakeholder follow-up interview and survey, project diaries and policy mapping—were developed to assess how stakeholders perceive the scale-up implementation process and adaptations to the roadmap. The role of context is considered relevant, and barriers and facilitators to scale-up will be continuously assessed.Ethics and dissemination Ethical approval has been obtained from the Institutional Review Board (ref. 1323/19) at the Institute of Tropical Medicine (Antwerp, Belgium). The SCUBY Project presents a comprehensive framework to guide the process and scale-up evaluation of complex interventions in different health systems. We describe how implementation outcomes, mechanisms of impact and scale-up outcomes can be a basis to monitor adaptations through a co-creation process and to guide other scale-up interventions making use of knowledge translation and co-creation activities.